Transformative Learning Through Group Coaching - Peters, Björn; Göhlich, Michael (Journal of Transformative Education, 2023)
Our study examines transformative learning outcomes of a group coaching format in a postgraduate program of a German University that is based on the cognitive-developmental approach to coaching. We administered a survey based on Kirkpatrick’s 4-Level Evaluation Model and its advancement by Alliger et al. that includes items from the Transformative Outcomes and Processes Scale. Findings suggest that the group coaching was effective on all levels and fostered transformative learning.
CRIS-Team Scopus Importer:2023-07-07
Keywords: group coaching; group work; Kirkpatrick’s evaluation model; personal transformation; transformative learning